Dynamics of Access to Pastoral Resources in a Farming Area (Western Burkina Faso): Unveiling Rights in Open Access Regimes - Alexis Gonin; Geoffroy Filoche; Philippe Lavigne Delville (International Journal of the Commons, 2019)
Several misunderstandings obscure the understanding of access to pastoral resources in farming areas of West Africa. Firstly, pastoral resources are often considered as commons, whereas they are mostly based on open access. Secondly, these open access regimes are under-studied and suffer from a poor understanding of what is a “right” in such regimes. This is an important issue, because grazing resources are disappearing in farming regions while fields for crops are extending, and because herders’ rights do not protect them from this adverse change in land use. Grounded on field work in western Burkina Faso, this article specifies herders’ rights of access in the area by drawing upon the concepts forged by Wesley Newcomb Hohfeld (1913). This American legal scholar sees rights as a relational issue, not as individual or collective entitlements. His analytical framework has been influential since the beginning of the 20th century and proves to be relevant to highlight farmers-herders relations. The article demonstrates that herders benefit from liberty of access rather than rights in the strictest sense of the word. Access to pastoral resources is weak because herders are subject to farmers’ power to change their land use from pastoral to agricultural.